DYNAMICS OF PERIODONTAL TISSUES MICROBIOCENOSIS UNDER THE COMPLEX TREATMENT OF CATARRHAL GINGIVITIS AND CHRONIC GASTRODUODENITIS IN THE ADOLESCENTS - Lisetska, I. S.; Rozhko, M. M.; Kutsyk, R. V. (International Journal of Medicine and Medical Research, 2019)
Background. The key links in the etiology and pathogenesis of periodontal tissue diseases are the quantitative and qualitative changes in the composition of the microflora of oral cavity, with the simultaneous deterioration of oral hygiene, reduction of local and general immunity, which occurs more often in the presence of somatic diseases. Objective. The aim of the research was to determine the clinical and microbiological efficacy of the developed treatment-prophylactic complex in the adolescents with catarrhal gingivitis and chronic gastroduodenitis before and after treatment. Methods. Changes were made to and before the treatment of clinical parameters, gingival microbiocenosis of 38 adolescents with generalized catarrhal gingivitis and chronic gastroduodenitis aged 12-18 years old, who comprised the main group. In the comparison group 25 adolescents of similar age diagnosed with generalized catarrhal gingivitis without any somatic diseases were involved. Results. It has been established that used combination (drug of plant origin with antimicrobial properties + dental gel with Metronidazole benzoate and Chlorhexidine digluconate + capsules of probiotics) yields the conventional treatment as well as exceeds it for examined clinical indicators and indexes. The treatment and prophylaxis with suggested complex have proved a significant positive effect on the gums microbiocenosis in adolescents with generalized catarrhal gingivitis and underlying concomitant gastroduodenitis. Conclusions. The suggested therapeutic and prophylactic complex provides a reduction in the massiveness and colonization frequency of the gum mucosa by pathogenic aerobic microflora (β-hemolytic streptococcus, golden staphylococcus, and yeast-like Candida fungi).